The Effect of Digital Leadership on the Enhancement of Organizational Creative Performance / A Survey Study in the Asia Cell Telecom Company in the Northern Region-Iraq - Zaker, Rabee Ali (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Organizations face increasing pressure to adapt leadership approaches in response to rapid digitalization and technological change. Specific Background: Digital leadership, encompassing digital vision, decision-making, execution, and guidance, has emerged as a strategic approach within the telecommunications sector to support organizational creative performance. Knowledge Gap: Despite growing scholarly attention, limited empirical evidence exists regarding how digital leadership simultaneously relates to exploratory and exploitative creative performance, particularly in developing economies and dynamic industries. Aims: This study examines the relationship between digital leadership and organizational creative performance in Asiacell Telecommunications Company in Northern Iraq. Results: Using a quantitative cross-sectional design with 88 valid responses analyzed through PLS-SEM, the findings reveal a strong and statistically significant positive relationship between digital leadership and organizational creative performance, with all dimensions contributing meaningfully. Novelty: The study provides empirical validation of digital leadership as a multidimensional construct that simultaneously supports both exploratory and exploitative creativity within a telecommunications context in a developing economy. Implications: The results highlight the importance for organizations to develop digital leadership capabilities to sustain creativity and maintain competitiveness in digitally transforming environments. Highlights:• Strong Statistical Relationship Identified Between Leadership Digitalization and Creative Outcomes• All Leadership Dimensions Jointly Contribute to Dual Forms of Organizational Creativity• Empirical Evidence Derived From Telecommunications Context in a Developing Economy Keywords: Digital Leadership, Organizational Creative Performance, Telecommunications Sector, Exploratory Creativity, Exploitative Creativity.